Anti-Inflammatory Properties of Flavone di-C-Glycosides as Active Principles of Camellia Mistletoe, Korthalsella japonica - Kim, Min Kyoung (Biomol Ther (Seoul), 2016)
The chemical components and biological activity of Camellia mistletoe, Korthalsella japonica (Loranthaceae) are relatively unknown compared to other mistletoe species. Therefore, we investigated the phytochemical properties and biological activity of this parasitic plant to provide essential preliminary scientific evidence to support and encourage its further pharmaceutical research and development. The major plant components were chromatographically isolated using high-performance liquid chromatography and their structures were elucidated using tandem mass spectrometry and nuclear magnetic resonance anlysis. Furthermore, the anti-inflammatory activity of the 70% ethanol extract of K. japonica (KJ) and its isolated components was evaluated using a nitric oxide (NO) assay and western blot analysis for inducible NO synthase (iNOS) and cyclooxygenase (COX)-2. Three flavone di-C-glycosides, lucenin-2, vicenin-2, and stellarin-2 were identified as major components of KJ, for the first time. KJ significantly inhibited NO production and reduced iNOS and COX-2 expression in lipopolysaccharide-stimulated RAW 264.7 cells at 100 μg/mL while similar activity were observed with isolated flavone C-glycosides. In conclusion, KJ has a simple secondary metabolite profiles including flavone di-C-glycosides as major components and has a strong potential for further research and development as a source of therapeutic anti-inflammatory agents.